Clinico- pathological profile and course of malignant pleural effusion in a tertiary care teaching hospital in western U.P. with special reference to lung cancer - Anurag Agrawal; Rajeev Tandon; Lalit Singh; Aakanksha Chawla (Lung India, 2015)
Background: Malignant pleural effusion is a major clinical problem associated with primary and metastatic pleural malignancies. Pleural effusions from an unknown primary are responsible for 7-15% of all malignant pleural effusions. Presence of malignant pleural effusion puts the patient in advanced stage and renders the prognosis as poor. Aim: In this study we intend to find out the incidence of malignant pleural effusion, its aetiology and clinical course in patients attending a tertiary care teaching hospital. Results: A total of 308 patients were included in this study. A majority of the patients were in age group 50- 70 years (median age = 58.8 years; range 32- 85 yrs). Male to female ratio was 2.5:1. The major primary cancers were lung cancer (135), lymphoma (40), breast cancer (36), female genital tract (30) gastrointestinal (21), and others (8). In 38 cases primary remained unknown. The yields of pleural fluid cytology, blind pleural biopsy, CT/USG guided pleural biopsy and thoracoscopy were 60%, 49%, 76% and 91% respectively. Chemical pleurodesis yielded complete response in 80%, incomplete response in another 13% patients. Only 136 (44%) cases could be followed up for minimum of 6 months. A majority of them (95, 69.85%) died. Conclusion: We conclude that malignant pleural effusion is a commonly misdiagnosed medical entity. Lung cancer is the commonest cause. Despite all efforts, in about 15% of the cases, primary remains undiagnosed. Thoracoscopy/pleuroscopy is a cost effective measure for diagnosis. Chemical pleurodesis provides expected results but mortality remains high.